(untitled) (Annals of Medical Research, 2021)
Aim: Decreased oxygen in cerebral tissues induces anaerobic glycolysis and lactate production increases. It has been demonstrated that blood lactate level is an independent risk factor for poor outcome in patients with acute ischemic stroke (AIS). In this study, the association between initial blood lactate level and short-term prognosis in patients with AIS treated with intravenous thrombolysis was evaluated.Materials and Methods: Three hundred and sixty one patients treated with intravenous thrombolytic treatment (IVT) were included in the study. Initial symptoms, comorbid diseases and localization of ischemia were recorded. Blood samples were obtained after stroke symptoms within 4.5 hours. Lactate levels were tested before IVT. Disability was calculated with National Institutes of Health Stroke Scale (NIHSS). At 24th and 72th hours, cerebral hemorrhagic transformation was evaluated with brain computed tomography. In-hospital mortality rate was determined. Patients were divided into 2 groups according to difference of NIHSS score (clinical improvement=NIHSS score decreased 4 points or more and no clinical improvement=other patients). Patients were divided into 2 groups according to lactate levels (low=lactate ≤2 mmol/L and high=lactate> 2 mmol/L).Results: A total of 361 patients, 188 (52.1%) female and 173 (47.9%) male were included in the study. Lactate level and base excess (BE) were higher in patients with severe disability (p 0.001). Serum pH and bicarbonate (HCO3) levels were lower in this group (p 0.001, p=0.006). Lactate cut off value was calculated as 1.72 (59% sensitivity, 58% specificity). Serum lactate level was higher in patients with cerebral hemorrhagic transformation (p=0.028). Lactate cut off value was calculated as 1.79 (56.0% sensitivity, 61.0% specificity).Conclusion: Lactate is a valuable parameter in ischemia. Blood lactate level is associated with disability and cerebral hemorrhagic transformation in patients with AIS treated with IVT.